Founders [compact disc, unabridged] : a novel of the coming collapse - Rawles, James Wesley (Brilliance Audio, 2012)
It's the near future and thanks to reckless banking practices, hyperinflation, a stock market gone mad, and the negligence of elected officials, the entire social, political, and economic infrastructure of America has collapsed. Chaos reigns in the streets, medical treatment is no longer available, and a dangerous group of men are at the helm of a false government. America's fate is in the hands of a few individuals who have the survival skills and forethought to restore the country.